The influence of nickel loading on reducibility of NiO/Al2O3 catalysts synthesized by sol-gel method (Chemical Engineering Research Bulletin, 2010)
The sol-gel method was used to synthesize nickel-alumina catalysts with various nickel loadings. Chemical and physical properties of support and supported nickel were characterized by TGA, DTA, EDX, SEM, BET, XRD and TPR techniques. Calcination temperature (500°C) was determined by performing thermogravimetric and differential thermal analysis on the samples. Energy dispersive X-ray (EDX) was used to determine the actual content of nickel on alumina. N2 adsorption test revealed that the specific surface area varied between 550 and 223 m2/g for pure alumina and 30%Ni/Al, respectively. X-ray diffraction patterns showed no peaks due to NiO species and NiO species were well dispersed on the support by formation of NiAl2O4 phase. Temperature-programmed reduction (TPR) indicated that the nickel species mainly presented in NiAl2O4 phase and small amount of NiO. In the 20 percent nickel loading, the surface NiAl2O4 phase, which is between NiO and bulk NiAl2O4 phases in terms reducibility, was formed considering as a successful result.Keywords: Nickel-alumina catalysts; sol-gel method; thermogravimetric analysis; dispersion of NiO; reducibilityDOI = 10.3329/cerb.v14i2.5052 Chemical Engineering Research Bulletin 14 (2010) 97-102